Reserva de desenvolvimento sustentável Rio Negro (AM) e sua relação com o turismo de base comunitária: perspectivas de gestão local na Amazônia e percepção das comunidades - SOUSA, Roberta Maria de Moura (Universidade Federal do Pará, 2018)
This thesis had as main objective to analyze the process of management of CommunityBased Tourism (TBC) implanted in the Rio Negro Sustainable Development Reserve (RDS) and its relation with the communities of Nossa Senhora do Perpétuo Socorro do Tumbira, Santa Helena do Inglês, São Sebastião do Saracá, São Thomé, Santo Antônio do Lago do Tiririca and Nossa Senhora do Perpétuo Socorro do Acajatuba, located on the right bank of the RDS belonging to the municipality of Iranduba (AM) composing the Mosaic of Protected Areas of Lower Rio Negro, considering the performance of the Amazonas Sustainable Foundation (FAS) and the State. In order to answer the questions that caused us concern, it was necessary to elaborate a theoretical-methodological reference that would enable us to understand the observations made in the field through a dialogue with the theory. Given this, we seek to base the study on theories that deal with tourism articulating with the notion of the use of territory, space and place as a social aspect. From a qualitative perspective, this research was carried out based on descriptive, exploratory studies, through bibliographical survey, documentary analysis and field research, with observation, interviews, oral narratives, participatory workshops for tourism planning and the construction of mental maps. The results revealed that in each community surveyed there are difficulties in planning the TBC and this is perpetuated mainly by the actions of the State, with regard to public policies in interpreting tourism from the economic point of view, distancing it from its social and environmental commitments. Likewise, it was possible to observe that the FAS, furthermore, acts to the State of Amazonas the implementation of governmental policies and projects that contemplate the tourist development. Although it seeks new sustainable practices through TBC, it is linked to a political process alien to the principles of sustainability, and uses environmental discourse to integrate into society and minimize the conflicts and dissatisfactions of traditional communities, embodied in participatory management. In this direction, decision-making bodies in the field of tourism planning and management promote relations of power and dependence under the logic of the domination of financial capital. In addition, it is believed that the residents of RDS Rio Negro who recognize and identify themselves as "local people" feel excluded from the process of planning and managing tourism activities. On the other hand, they believe TBC is a potential vehicle for social transformation and as an alternative to nature conservation, social inclusion, in addition to being able to generate income for the locality. Finally, it was observed that the organizational form of tourism meets individual preferences, so there is no intention to promote development from a local perspective.